2018
DOI: 10.1111/head.13435
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders Among People With Migraine: Results From the Chronic Migraine Epidemiology and Outcomes (CaMEO) Study

Abstract: Objectives.— We examined the cross-sectional association of sleep apnea and indices of sleep quality with both episodic migraine (EM) and chronic migraine (CM). Background.— Sleep apnea and abnormal patterns of sleep, such as insomnia, were associated with migraine onset, severity, and progression in previous research. Methods.— The Chronic Migraine Epidemiology & Outcomes Study, a longitudinal study, used a series of web-based surveys to assess migraine symptoms, burden, and patterns of health care utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 64 publications
1
55
0
1
Order By: Relevance
“…Many medical conditions are more common in people with migraine compared to the general population [33]. There is a small body of literature examining rates of single medical conditions among people with and without migraine, and over the past decade, a growing body of literature has emerged examining the effect of headache day frequency on rates of migraine comorbidities and the effects of selected comorbidities on headache progression [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28]. After adjusting for sociodemographic variables, the cohort with migraine was about three times more likely to report a medical diagnosis of insomnia, depression, anxiety, and gastric ulcer/GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many medical conditions are more common in people with migraine compared to the general population [33]. There is a small body of literature examining rates of single medical conditions among people with and without migraine, and over the past decade, a growing body of literature has emerged examining the effect of headache day frequency on rates of migraine comorbidities and the effects of selected comorbidities on headache progression [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28]. After adjusting for sociodemographic variables, the cohort with migraine was about three times more likely to report a medical diagnosis of insomnia, depression, anxiety, and gastric ulcer/GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity is the greater than chance association between the two conditions in the same individual [2]. There are many comorbidities associated with migraine including cardiovascular disorders (i.e., stroke, myocardial infarction [3][4][5][6][7][8][9][10], psychiatric disorders (i.e., depression, anxiety, panic disorder, bipolar disorder, personality disorders, suicide attempts) [11][12][13][14][15][16][17][18][19][20][21], neurologic diseases (i.e., epilepsy), sleep conditions (i.e., insomnia, restless leg syndrome, sleep apnea, poor sleep quality and duration) [22][23][24], inflammatory conditions (i.e., allergic rhinitis, asthma) [25,26] as well as chronic pain conditions (i.e., fibromyalgia) [27], among many others [28]. Many comorbidities have been identified as risk factors for progression to chronic migraine [29] and recent work has shown that the combination of comorbidities or "multimorbidity" is associated with medication overuse and new onset CM [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…‡The survey asked respondents to report fear of next migraine attack on a 1 to 5 scale, where 1 = not fearful at all, 2 = a little fearful, 3 = somewhat fearful, 4 = very fearful, and 5 = extremely fearful. 19 and that people with migraine worry about a next migraine attack, 20 experience low sleep quality, 21,22 and rely on family for help. 23,24 Our study is unique in that it also provides this data by respondents' preventive treatment history.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact cause of this type of headache still remains unclear [6,7]. The most extensively studied epidemiological association in OSAS patients was between headaches and snoring [10,11]. MH is not specific and may complicate many other diseases such as anxiety and depression, circadian rhythm disorders, unspecified dyssomnia, and last but not least, arterial hypertension [11][12][13].…”
Section: Introductionmentioning
confidence: 99%